2022
DOI: 10.1007/s00269-022-01214-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal genesis and growth of the banded agates from the Allumiere-Tolfa volcanic district (Latium, Italy)

Abstract: In this work, we studied the hydrothermal agates from the Neogene–Quaternary volcanic district of Allumiere-Tolfa, north-west of Rome (Latium, Italy) using a combination of micro-textural, spectroscopic, and geochemical data. The examined sample consists of (1) an outer cristobalite layer deposited during the early stages of growth, (2) a sequence of chalcedonic bands (including i.e., length-fast, zebraic, and minor length-slow chalcedony) with variable moganite content (up to ca. 48 wt%), (3) an inner layer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…The presence of Bambauer quartz (Figure 4E) in vein agates indicates its formation in hydrothermal fluids characterized by fluctuations of silica concentrations and pH conditions [6,28,[53][54][55][56]. It is supposed that these fluctuations in physicochemical conditions…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of Bambauer quartz (Figure 4E) in vein agates indicates its formation in hydrothermal fluids characterized by fluctuations of silica concentrations and pH conditions [6,28,[53][54][55][56]. It is supposed that these fluctuations in physicochemical conditions…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Bambauer quartz (Figure 4E) in vein agates indicates its formation in hydrothermal fluids characterized by fluctuations of silica concentrations and pH conditions [6,28,[53][54][55][56]. It is supposed that these fluctuations in physicochemical conditions of hydrothermal fluids are responsible for the frequent alterations of different silica phases [53] in vein agates, especially in the Mehane and Rasovača agate occurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Bands with less intense colouration are composed primarily of granular macrocrystalline quartz. Specifically, the macrocrystals have micrometre-sized lamellae, due to the episodic stages of crystal growth, typical of the so-called 'Bambauer quartz' (Bambauer et al, 1961;Conte et al, 2022) and a feathery aspect at the margins of quartz grains (Adams, 1920;Dong et al, 1995). Granular quartz occurs with different orders of magnitude in size and exhibits undulose extinction (Adams et al, 1984), related to the granules being polycrystalline (Adams et al, 1984), denominated strained quartz (Jóźwiak-Niedźwiedzka et al, 2017).…”
Section: Optical Microscopymentioning
confidence: 99%
“…The distribution of molecular water in the banded area of agates is not homogenous. The spatial water distribution across the growing sequence (presented by the alternation of moganite-rich and moganite-poor chalcedony layers, and macrocrystalline quartz) of the agate sample from the Allumiere-Tolfa volcanic district (Latium, Italy) was studied by Conte and his colleagues using coupled Raman and FT-IR micro-spectroscopy [49]. In particular, these authors revealed an anticorrelation between the moganite content and water signal.…”
Section: Water In Quartz and Chalcedonymentioning
confidence: 99%
“…The 3585 cm −1 infrared absorption band is occasionally observed in natural and synthetic rock crystals, including amethysts [50]. It was also recognized in the IR spectra of agates from young volcanic hosts, but has not been found in the IR spectra of agates in volcanics aged from 1100 to 89 Ma [44,48,49]. Up to now, the assignment of this band has been quite vague.…”
Section: Water In Quartz and Chalcedonymentioning
confidence: 99%